'Flying the late King's Colours': Royalist privateering during the First Anglo-Dutch War, 1652–1654. Issue 1 (2nd January 2023) - Abernethy, Jack
Abstract : This article examines the service of royalist privateers during the First Anglo-Dutch War, 1652–4. Most scholarship has focused on the remnants of Prince Rupert's royalist fleet and its eventual retreat to France in 1653, which is taken as the conclusion of the naval theatre of the Wars of the Three Kingdoms, 1639–55. Rather than focusing on Prince Rupert, this article identifies the principal royalist privateers operating outside of his fleet. In turn it demonstrates that these royalists pursued a vigorous guerre de course against the Commonwealth and Protectorate, continuing the Civil Wars at sea. This article demonstrates the ways in which the Cromwellian navy dealt with these privateers and concludes by arguing that they operated within a wider royalist naval strategy spearheaded by the exiled Charles II and James, Duke of York.